2004
DOI: 10.1038/sj.mp.4001516
|View full text |Cite
|
Sign up to set email alerts
|

β-sheet breaker peptide prevents Aβ-induced spatial memory impairments with partial reduction of amyloid deposits

Abstract: Current evidence supports the notion that b-amyloid deposits or Ab intermediates may be responsible for the pathogenesis in Alzheimer's disease (AD) patients. In the present work, we have assessed the neuroprotective effect of the chronic intraperitoneal administration of a five-amino-acid b-sheet breaker peptide (iAb5p) on the rat behavioral deficit induced by the intrahippocampal Ab-fibrils injection. At 1 month after the injection, animals showed a partial reduction of the amyloid deposits formed and a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 42 publications
3
124
0
Order By: Relevance
“…Different degrees of astrocyte reactivity were observed by GFAP immunostaining, after the animals were injected with Ab fibrils alone, they presented a strong glial reaction with the presence of classical appearance of hypertrophic astrocytes. 16 Thus, at least until 18 days after coinjection of HYP plus Ab, the decrease of the reactive astrocytes was correlated with the protection of the granular cell layer loss. On the other hand, the microglial activation was analyzed, with the idea to associate it to a proinflammatory process.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Different degrees of astrocyte reactivity were observed by GFAP immunostaining, after the animals were injected with Ab fibrils alone, they presented a strong glial reaction with the presence of classical appearance of hypertrophic astrocytes. 16 Thus, at least until 18 days after coinjection of HYP plus Ab, the decrease of the reactive astrocytes was correlated with the protection of the granular cell layer loss. On the other hand, the microglial activation was analyzed, with the idea to associate it to a proinflammatory process.…”
Section: Discussionmentioning
confidence: 90%
“…The analysis of the behavioral performance showed that animals injected with Ab had the highest latency values (black circles), in accordance with the neurotoxic effects of Ab. 16 The animals injected with Ab and HYP present significantly lower escape latency values than animals injected with Ab (Figure 3a), indicating that HYP was able to reduce the cognitive impairment on spatial memory performance induced by Ab. In contrast, animals injected with aCSF or HYP did not show significant difference in their escape latency values mainly during the second week of training (Figures 3a and 4a), suggesting that HYP neither induces spatial learning impairments nor enhances the cognitive status of the rat is also the case for the animals injected with OHP-Gal or OHP-Li (Figure 3c and e).…”
Section: Hyp Avoids the Formation Of Cr-positive Amyloid Deposits Indmentioning
confidence: 92%
See 3 more Smart Citations